Enhancing Speaking Skills Through Arabic Language Teaching within Islamic Studies Materials Among Students - Wardhana, Delly; Bahruddin, Uril; Sutaman, Sutaman; Imaduddin, M. Firdaus; Babiker, Gareeb Allah Babiker Mustafa (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
This study aims to explore three main aspects: (1) describing the teaching of Arabic within Islamic studies subjects at Imam Al-Shafi’i Institute in Metro, Lampung, (2) identifying the factors influencing Arabic language education within Islamic studies subjects at the institute, and (3) assessing the contributions of this educational approach in improving students' speaking proficiency. This research employs a qualitative approach with a descriptive research method. Data collection techniques include field observations, interviews, and document analysis. The data are analyzed through processes of data collection, condensation, presentation, and conclusion drawing. The findings of the study indicate that Arabic is taught as part of Islamic studies subjects, where the textbooks used are written in Arabic, instructors teach in Arabic, and language exercises are integrated into the curriculum. Several factors contribute to the improvement of students' speaking skills, including the linguistic competence of teachers, students' religious motivation, and institutional efforts to promote Arabic. Furthermore, the integration of Arabic language instruction within Islamic studies has played a significant role in enhancing students’ speaking proficiency, enabling them to speak fluently.